Bond performance of sand-coated and ribbed-surface glass fiber reinforced polymer bars in high-performance concrete. (December 2021) - Lu, Jennifer; Afefy, Hamdy M.; Azimi, Hossein; Sennah, Khaled; Sayed-Ahmed, Mahmoud
Abstract: This paper presents an experimental study on the bond characteristics of both sand-coated and ribbed-surface glass fiber reinforced polymer (GFRP) bars embedded in high-performance concrete (HPC). A total of 145 pullout tests were conducted in order to examine the effect of varying parameters on the bond characteristics, namely: embedment length, bar diameter, surface treatment, concrete cover and bond stress-slip relationships. The experimental results showed that the sand-coated bars exhibited better bond strength than that developed by the ribbed-surface GFRP bars, which entails lower development lengths. Besides, it was found that the increase in bar diameter was accompanied by a decrease in the bond strength. Furthermore, experimental results displayed a slight increase in the bond strength as the concrete cover increased from 40 to 60 mm. Finally, based on the material properties of the used GFRP bars and concrete patch, using HPC surrounding both sand-coated and ribbed surface GFRP bars resulted in unfavorable modes of failure. That is because in most cases GFRP bars failed by either shearing of the ribs of the ribbed-surface bars or peeling of the sand-coating layer out of the core diameter for the sand-coated bars.